A first introduction to data science education in secondary schools: Teaching and learning about data exploration with CODAP using survey data. (25th June 2021) - Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Budde, Lea
Abstract: In this paper, we will describe an introduction to Data Science for secondary school students. We will report on the design and implementation of an introductory unit on "Data and data detectives with CODAP" in which secondary school students used the online tool CODAP to explore real and meaningful survey data on leisure time activities and media use (so‐called JIM‐PB data) in a statistical project setting as a starting point for data science. The JIM‐PB data set served as a valuable data set that offered meaningful and exciting opportunities for data exploration for secondary school students, and CODAP proved to be a valuable tool for the first explorations of this data.